IMMU-32. RNA-NANOPARTICLE VACCINES MEDIATE T CELL TRAFFICKING NECESSARY FOR BBB PASSAGE AND ANTI-GLIOMA IMMUNE RESPONSE. (11th November 2019) - Mendez-Gomez, Hector; Wummer, Brandon; Grippin, Adam; Weidert, Frances; Huang, Jianping; Deleyrolle, Loic; Mitchell, Duane; Sayour, Elias
Abstract: BACKGROUND: The blood-brain barrier (BBB) remains a potent obstacle for development of new therapies against glioblastoma (GBM). While activated T cells can cross the BBB, immunotherapy has yet to be fully unlocked for malignant brain tumors due their heterogeneity and immunosuppressive microenvironments. To overcome these challenges, our group has developed a novel treatment platform, which leverages the use of a clinically translatable nanoparticles (NPs) combined with personalized tumor derived mRNA to peripherally activate T cells against a heterogenous source of tumor antigens and reprogram the intratumoral milieu into an immune activated state. OBJECTIVE: We sought to assess if RNA-NPs could activate systemic/intratumoral dendritic cells (DCs) and mediate a peripheral T cell response that could penetrate the GBM microenvironment. RESULTS: We uncovered that RNA-NPs elicit potent innate immunomodulating effects through release of interferon-α (IFN-α) from plasmacytoid DCs (pDCs). After only a single RNA-NP vaccine, the bulk of systemic and intratumoral DCs in mice display an activated phenotype; DCs, harvested from intracranial tumors, elicit expansion of antigen specific T cell immunity. Tumor-specific RNA-NPs elicited enhanced survival outcomes in immunocompetent animals bearing NF-1/p53 mutant gliomas with increased intratumoral memory CD8 + T-cells. Unlike immune checkpoint blockade (anti-PD-L1 mAbs), we found that RNA-NPs increase LFA-1 on peripheral CD8 splenocytes, which is necessary for activated T cell passage across the BBB. RNA-NPs also increased CCR2 on peripheral CD8 cells, which was dependent on IFN-α/β, as the percentage of CCR2 + CD8 + splenocytes and anti-tumor activity (mediated by RNA-NPs) was abrogated in animals receiving concomitant type I IFN receptor (IFNAR1) mAbs. CONCLUSION: Since LFA-1 is important for T cell trafficking across the BBB and CCR2 may promote chemotaxis to the brain (as GBMs are known to secrete CCL2), RNA-NPs may offer a new treatment modality and immunologic mechanism for unlocking peripheral T cell immunity against malignant gliomas.